L’ ’amour fou’ tra spaesamento e straniamento in due scrittrici siciliane: Rosina Muzio Salvo e Cettina Natoli - Bombara, Daniela (Incontri. Rivista europea di studi italiani, 2021)
Amour fou between displacement and estrangement in two Sicilian writers of the Nineteenth Century Rosina Muzio Salvo and Cettina Natoli This research aims at investigating the topos of love as deep and extreme passion, in opposition to social stereotypes, in two novels by two Sicilian female writers of the Nineteenth Century, Adelina (1845) by Rosina Muzio Salvo (1815-1866) and Margherita Royn (1886) by Cettina Natoli (1867-1913). In Adelina amour fou is in conflict with the patriotic needs and the moralism of the newborn middle-class society; in Margherita Royn, an overliterary, different kind of love clashes with the materialism and commercialization which dominate in late Nineteenth century. Adelina’s displacement is highlighted by the structure of the polyphonic epistolary novel, in which the protagonist’s ‘reasons of the heart’ are opposed to the opinions of all the other characters; according to a process of Verghian estrangement (Luperini, 1974), they convey a distorted picture of her passion and consider it a weird, unacceptable fact. Margherita is able to see reality only through an overly literary lens of extreme sentimentality; her isolation is manifest in the depiction of her body, consumed by an adulterous passion which contrasts with her husband’s rough physicality; overcome by jealousy, he will end up killing her.